Yadava dialect of Tamil - Jayapal, S., 1947- (Publication (Annamalai University. Dept. of Linguistics) ;, 1978)
Grammar of the dialect spoken by the Yadava or Idair (shepard and cattle grazing community) of South Arcot District, Tamil Nadu.